PROMOTING MENTAL HEALTH CARE IN PAKISTAN WITH “LADY HEALTH WORKER APPROACH” (The Research of Medical Science Review, 2024)
Objective:Mental health disorders contribute a major part of global disease burden. Statistics of 2016-17 show that globally, around 450 million people are suffering from mental diseases that constitutes 14% of the total disease burden. In Low- and MiddleIncome Countries (LMIC) like Pakistan, mental health issues are somewhat ignored due to limited resources and lack of awareness. Objective of this review to analyze what are the current policies in Pakistan for mental health care and how Lady health workers can contribute to mental health care? Method: Research question and search terms were designed following PICOS. This is a literature review following extensive online database search using EBSCOhost, PUBMED, CINHAL ultimate and online libraryResults: Lady Health Workers are the most prominent cadre in delivering primary health care. LHWs fight the discrepancy in the rural areas and the lack of awareness in the rural community by delivering services at the doorstep. LHWs cover almost 60% of the rural population.Conclusion: LHWs can work vertically with reproductive as well as mental health programmes at a time within limited budget cost-effectively. However, this integration program needs proper knowledge, skills and training program designed and implemented